Role of Board- Manager Relation on Cooperative Performance - Rakhal, Dhaneshwar (Janapriya Journal of Interdisciplinary Studies, 2018)
Cooperatives are based on the philosophy of equality and mutual help i.e. ’All for each and each for all’. They cover a wide range of development services in Nepalese context. The members of a cooperative elect a board of directors in its general meeting for the day to day operation. The board prepares policy and procedures, and appoints manager(s) to implement the policies and run the program. One of the internal issues in saving and credit cooperatives is the relationship between managers and the board of directors which affects on the performance level of the cooperative. In this regard, the main objective of this paper is to assess the relationship between managers and the board of directors, and its impact on the performance of saving and credit cooperatives in Pokhara. The study also covers the managers’ feelings of job satisfaction, career development opportunities, and responsibilities of board of directors and managers. Out of 212 savings and credit cooperatives in Pokhara Sub-metropolitan, 77 cooperatives were selected as sample. A questionnaire survey with the mangers was carried out to derive the primary information, and annual audited reports are used as secondary sources of data. The results indicate that board-manager relation does not affect the responsibilities of board of directors and managers, and academic qualifications of managers are positively related to performance of the cooperatives. Finally the paper concludes that the board manager relationship is positively related to return on assets of the cooperatives. Janapriya Journal of Interdisciplinary Studies, Vol. 6 (December 2017), page: 60-77